Revisiting Property Ownership Ontology in Islamic Legal Philosophy and Maqāṣid al-Syarī‘ah - Restu Hilwani Azra' (IAI Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2025)
This study examines the ontology of property ownership in Islamic legal philosophy and its relevance to the maqāṣid al-syarī‘ah. The research problem stems from the tendency of studies on property ownership to focus more on normative and legal aspects, while the ontological foundation of ownership as a divine trust has not yet been systematically examined. This study aims to explain the nature of property ownership in Islamic law and to assess its alignment with the objectives of the Sharia, particularly the protection of property (ḥifẓ al-māl). This study employs a normative legal method with a conceptual-philosophical approach and the framework of maqāṣid al-syarī‘ah. Data were obtained from classical and contemporary Islamic legal literature and analyzed qualitatively and descriptively using a deductive framework. The results indicate that property ownership is not absolute but rather a trust from Allah SWT that entails moral and social responsibilities. Consequently, ownership is constrained by ethical values, justice, and social distribution obligations. The integration of the ontology of ownership and the maqāṣid al-syarī‘ah affirms that ḥifẓ al-māl not only protects individual property rights but also directs the social function of wealth to realize justice and the public interest.